Gender and Hypertantion (Data analysis of The Indonesia Basic Health Research 2007) - Bantas, Krisnawati; Gayatri, Dwi (UI Scholars Hub, 2019)
The objective of this study was to examine whether there was a gender difference in the occurrence of hypertension in Indonesian people, after controlling for individual and environment factors. Data were ob tained from the Indonesia Basic Health Research 2007 and a cross sectional design was used. Samples consisted of 13.262 men and women age 15 years or more. A multilevel logistic regression was used to ana lyze the data. There was a statistically significant association between gender and hypertension. Women were less likely to have hypertension than men (OR 0.86 P value < 0.0033). There was an interaction between variable of gender and variable of age. It suggested that the probability of having hypertension in women and men was varied by the strata of age. In the strata of age more than 60 years, women were more likely to have hypertension than men (OR 1.25, P value 0.0065); in strata of age 30-59 years, there was no difference of having hypertension between women and men (P value > 0.05); in strata of age <30 years, women were less likely to have hypertension than men (OR 0.67 Pvalue 0.0000). Among women, there was an increased of having hypertension with age. Age of e” 60 years was the highest risk of having hypertension. Among men, there was an increased of having hypertension with age, but at in the age of e” 60 years the increased risk of having hypertension was not as high as in women.